Rastreamento da Doença de Fabry em uma população de pacientes renais crônicos em hemodiálise no estado de Sergipe - Mendonça, Emanuelle Nabuco Queiroz Cardoso de (2014)
Introduction: The FD is an inborn error of metabolism linked to the X chromosome, where deficiency or absence of the enzyme α-Gal A generates progressive accumulation of glycosphingolipids in various organs. Whereas FD evolves with multisystemic progressive character, more severe in males and potentially treatable, this study aimed to trace the FD in adult men on hemodialysis undiagnosed particular program. Method: Tracking FD by determining the activity of plasma α-Gal A blood collected on filter and diagnosis through analysis of specific mutations in those with decreased plasma activity confirmation paper. Results: Of the 155 patients, 9 showed a decrease in plasma activity of α-Gal A, 7 were subjected to analysis of specific mutations and only 1 had a positive diagnosis for FD. Discussion: The prevalence of FD found in the study is similar to other national papers. Chronic renal failure on hemodialysis undiagnosed defined programs form a group at high risk for FD. Low enzyme activity did not confirm the disease, since false-positive diagnoses were found. The clinical manifestations are not unique to FD, hindering early diagnosis. Conclusion: Tracking the FD through the analysis of the enzyme α Gal A activity was useful and practical in chronic renal failure patients on hemodialysis. It is suggested that this becomes routine investigation in those individuals with CKD without a confirmed etiologic diagnosis, so that if diagnosed, can be treated, along with their family members also affected.